Infestation, damage and control of harmful insects on upland rice - Ferreira, Evane; Zimmermann, Francisco José P.; Martins, José Francisco de Silva (Pesquisa Agropecuaria Brasileira, 1994)
Several insect pests infested the plants of an experiment installed at CNPAF, with the rice cultivar IAC-47, using two planting densities. Reduction on grain yield due to insect feeding were estimated on 1.606 kg/ha. The largest damage were caused by rhizophilous termites (65 4%) and lesser cornstalk borer (31,6%). Systemic carbamate insecticides commonly used in seed treatment raised the grain yield in 696 kg/ha or 60,1% of what was expected on the abscense of insect pest.